Critical Disability Discourses: New Vision and Managing Editor Self-Introduction - Greg Procknow (Critical Disability Discourses, 2025)
The new vision of Critical Disability Discourses CDD creates an academic space where emerging disability studies researchers will make valuable contributions to expanding critical disability scholarship. CDD mentors junior disability studies scholars, graduate students, postgraduates, and early-career academics as they make their first forays into peer-reviewed publishing with CDD. This approach will occur early in the managerial review process, when vetting the suitability of submissions before assigning them to peer reviewers. This mentoring arrangement has enabled us to expand the journal’s output successfully. Regarding output, CDD commits to publishing two issues per volume year. Each issue will comprise 5-7 original research articles, 1-2 perspective pieces, and 1-2 book reviews. CDD reaffirms its commitment to being bilingual, offering audiences and authors translated titles, abstracts, and keywords in French. CDD is committed to publishing ‘accepted’ pieces on our website on a rolling basis as they become ready. This includes reiterating our commitment to timely peer-review turnaround times, copyediting, and publication. All pieces henceforth will be published with an assigned DOI. CDD has assembled an experienced and well-rounded team of Editorial Board members, including a dedicated Arts-based editor, English language copyeditor, and a French language copyeditor.